THE PROBLEM OF INFORMATION STRESS AND STRESS RESISTANCE AMONG TODAY'S STUDENTS - Hamidaxon Tohirova; Mirkarim Raimdjanov (Web of Journals Publishing, 2024)
In this article, the information about the factors that cause informational stress in today's student, the conditions that affect the physiological course of this process in students, and the theoretical information about how they take place are theoretically analyzed.
Keywords: Stress, information stress, educational stress, information flow, time shortage, information pollution, student.